Analysis Of Rme Learning Models In Improving Mathematics Learning Outcomes Of Elementary School Students: Analisis Model Pembelajaran Realistic Mathematic Education (RME) Dalam Meningkatkan Hasil Belajar Matematika Siswa SD - Lestari, Andria Putri; Putra, Deni Adi; Faradita, Meirza Nanda (Pedagogia : Jurnal Pendidikan, 2020)
The learning model has an important role in the implementation of learning activities that will be carried out by educators. Learning models can help educators in achieving predetermined learning goals. This study aims to analyze the application of the Realistic Mathematic Education (RME) learning model in improving mathematics learning outcomes of elementary school students. This type of research is qualitative research using meta-analysis methods. This research begins by formulating research problems, searching for relevant data or journals available in electronic media (Google Scholar) for data analysis. Data collection techniques are obtained from searching journals that are relevant to the research to be analyzed which are available in electronic media (Google Scholar). Data from search results obtained 10 relevant journals. Based on the analysis of learning models Realistic Mathematic Education (RME) can improve student learning outcomes with a total percentage reaching 82.77%. Internal factors (physical and spiritual) and external factors (family, school, and community) can also affect learning outcomes obtained by elementary school students. Based on this research, the application of the Realistic Mathematic Education (RME) learning model for elementary school students can be a suggestion to be applied and developed in elementary schools so that it can improve student learning outcomes.